قرآن و سنت میں سماجی تعاون کی ٍتعلیمات اور عصرحاضر میں ان کی اہمیت: Teachings of social cooperation in Qur’an and Sunnah and their importance in the present era - Dr. Hafiz Muhammad Ahmad; Dr. Muhammad Shahid (MEI, 2023)
Islam is a complete code of life and is religion of nature.That is why mutul co.opration is focussed in its teachings. In Holy Quran Almighty Allah has stressed to co.oprate for righteausness and not co.oprate for agression and sins. Holy prophet (SAW) decleard the whole ummah as one body. In this research peper different islamic injunctions regrading mutual co.operation are ellaborated. Quranic verses, Hadiths and views of theologies are analysed. This article will help to motivate the society in eradication of social evils and problems by mutual cooperation. More over different types and aspects of human services are also analyzed in this article. If people follow the Islamic concept of mutual cooperation, this society will become prosperous and comfortable.